The Effect of the Spread of Coronavirus (COVID-19) on Stock Markets: The Case of Amman Stock Exchange (ASE) - Ghazi Aldeki, Raneem (Jordan Journal of Business Administration, 2023)
This paper has analyzed the movement of the Amman Stock Exchange (ASE) during the COVID-19 pandemic. The paper has used time-series analysis using the Vector Autoregression (VAR) model using data from Jan. 1, 2020 to May 31, 2022. It was found that the number of new cases of coronavirus infection eight days ago affects the performance of the market index with an inverse relationship. Also, the ambiguity bias ten days ago affects the performance of the market index with an inverse relationship. The study recommends investors to speculate on the Amman Stock Exchange, because, for about a week, investors can speculate without being affected by the drop in stock prices as a result of the coronavirus pandemic. The Amman Stock Exchange is a suitable environment for investment in times of crises. The study also recommends the foreign investment in the Amman Stock Exchange, because the negative impact of the spread of the coronavirus on the financial market is low compared to other markets that witnessed a significant deterioration in their stock prices when the pandemic appeared, where the negative market reaction was strong during the early days of the pandemic.